Faster onset time of supraclavicular brachial plexus block using local anesthetic diluted with dextrose - Lim,Hong Jin (2016)
Abstract Background and objectives: A high sodium concentration is known to antagonize local anesthetics when infiltrated around neural tissue. Thus, we hypothesized that the onset time for sensory and motor blockade, in supraclavicular brachial plexus block using ropivacaine diluted with dextrose would be shorter than with saline. Methods: Patients scheduled for upper limb surgery were randomized to receive ultrasound guided supraclavicular brachial plexus block with 0.5% ropivacaine. Evaluation of sensory and motor blockade was performed every 5 min for 60 min. Patients were followed-up on postoperative day 1, and between days 7 and 10 for the presence of any complications. Twenty-five patients in each group were analyzed. Results: Mean time for onset of analgesia for the dextrose group was 37.6 ± 12.9 min while the mean time for the saline group was 45.2 ± 13.9 min with a p-value of 0.05. The effect size was 0.567, which was moderate to large. No major complications were observed. Conclusion: We conclude that there was a decrease in onset time of analgesia when dextrose was used as a diluent instead of saline for ultrasound guided supraclavicular block.